2016
DOI: 10.1111/jan.13174
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative meta‐synthesis: the experience of chronic pain across conditions

Abstract: The findings in this review suggest there are similarities in the experience of chronic pain across a range of conditions that have implications for the development of transdiagnostic pain management strategies and interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 72 publications
(107 reference statements)
4
60
2
2
Order By: Relevance
“…Somewhat in contrast to certain previous findings (e.g. Crowe et al, 2017 ; Sorensen and Christiansen, 2017 ), which suggested that people were primarily motivated to maintain existing lifestyles and relationships, our data pointed to a movement in some participants to, instead, reformulate their lives, support networks and roles around fibromyalgia. The data suggested that an important part of new relationships was the sense of understanding and validation which was lacking elsewhere.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Somewhat in contrast to certain previous findings (e.g. Crowe et al, 2017 ; Sorensen and Christiansen, 2017 ), which suggested that people were primarily motivated to maintain existing lifestyles and relationships, our data pointed to a movement in some participants to, instead, reformulate their lives, support networks and roles around fibromyalgia. The data suggested that an important part of new relationships was the sense of understanding and validation which was lacking elsewhere.…”
Section: Discussioncontrasting
confidence: 99%
“…Often for the first time in the participants’ lives, their body had become discordant with not only their own intentions but also the social and physical world around them. Two themes outlined in Crowe et al’s (2017) review of chronic pain studies, termed ‘body as obstacle’ and ‘disrupted sense of self’, which describe how bodily symptoms interfere with lifestyle and identity, have resonance with our themes describing changes to participants’ family roles and working identity. Frustration and depression are commonly described consequences of these disruption of activities, goals and aspirations in previous work (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Reviews, syntheses and meta syntheses can be found in diagnosis related groups i.e. such as low back pain (Bunzli, Watkins, Smith, Schutze, & O'Sullivan, 2013;Froud et al, 2014;MacNeela, Doyle, O'Gorman, Ruane, & McGuire, 2015;, fibromyalgia (Sim & Madden, 2008) and in long-term musculoskeletal pain conditions (Crowe et al, 2017;Löfgren, Schüldt Ekholm, Schult, & Ekholm, 2016;Osborn & Rodham, 2010;Toye et al, 2013;Toye, Seers, Hannink, & Barker, 2017).…”
Section: The Patients' Experience Of Long-term Painmentioning
confidence: 99%
“…However, to date, there are no veteran or military personnel-specific coping scales. Whilst the National Institute for Clinical Excellence does advocate that CP management needs to incorporate valid assessment measures (Grady, 2015), general coping scales have validity and reliability issues (Crowe et al, 2017;Donoghue, 2005). Furthermore, questionnaires are often only administered once rather than longitudinally, so they may not factor stages of coping.…”
Section: How Army Veterans Cope With Chronic Pain: a Grounded Theory mentioning
confidence: 99%